Forearm bone mineralization in recently diagnosed female adolescents with a premenarchal onset of anorexia nervosa. Issue 8 (6th April 2016) - Roggen, Inge; Vanbesien, Jesse; Gies, Inge; Van den Eede, Ursula; Lampo, Annik; Louis, Olivia; De Schepper, Jean
ABSTRACT: Objective: Data available on bone mineralization by peripheral quantitative computed tomography (pQCT) in adolescents with an early onset anorexia nervosa (AN) is limited. We investigated whether a disturbed bone mineralization can be observed at the distal radius in recently diagnosed female adolescents with AN and a premenarchal onset of this disease. Method: Twenty‐four premenarchal patients with AN and 22 healthy females which were age and height matched, were selected from our reference database; both groups underwent a pQCT bone assessment at the distal radius of the nondominant arm. Results: The patients age ranged between 13.3 and 18.4 years. Their percent weight loss ranged between 5 and 36% (median 23%) and occurred within the preceding 3 to 44 months. Trabecular volumetric bone mineral density of the patient group was significantly lower than the comparison group (185.6 ± 30.2 vs.209.3 ± 34.0 mm 2 ; p = 0.02). Bone cross‐sectional area, bone mineral content, total volumetric bone mineral density and periosteal circumference were also lower, albeit not significantly. The bone parameters were unrelated to the under nutrition severity and duration. Discussion: In premenarchal patients with AN the trabecular bone mineralization of the forearm is significantly reduced, this might be an early indicator of altered bone mineral accrual. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2016; 49:809–812)